Contributions to the study of the elementary chemical composition of the principal macrophytes along the Romanian coast of the Black Sea - Roșoiu, Natalia; Bologa, Alexandru S. (Cercetări Marine - Recherches Marines, 2026)
The seasonal variations of Na+, K+, Ca2+ and Mg2+ contents of Enteromorpha linza. Cladophora sericea, Cl. Vagabunda, Cystoseira barbata, Ceramium elegans and Zostera marina + Z. nana are presented; the concentration of these elements varies according to their taxonomic pertaining, provenience location and season.